(untitled) (Research, Society and Development, 2021)
Introduction: A COVID-19 pandemic prompted the world to adopt containment measures. Or the emergence of new practices also brought with it other relationships of coexistence among university students with the adoption of emerging and urgent practices, or distance education. Some tools are important for the development of two-student learning and interaction between faculty and students, within academic centers and academic leagues. Objective: Evaluate the impact of the changes caused by the pandemic in the activities of undergraduate students, analyzing the insertion of remote activity in the student’s life. Methods: An integrative literature review. The present work was guided by the following guiding question: “What is the impact of remote activities of academic leagues in the context of teaching-learning in undergraduate courses”? Results: The six selected articles are all in Portuguese and both present an experience report-type approach, four of them were published in 2020, while the other two in 2021. Table 1 shows the harmony of the included studies at work for better visualization of content and results. Conclusion: It is very important to emphasize that academic leagues promote an increase in the potential for transforming the scenario of university centers. This characteristic was more evident during the pandemic, as the routine of all students and professionals in the health area began to change.